2022
DOI: 10.9734/jpri/2022/v34i37a36194
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia is an Independent Predictor of Rapid Progressive Disease in Patientswith Chronic Liver Disease

Abstract: Introduction: In chronic liver disease (CLD), the lipid profile biomarkers are altered because of decreased lipoprotein biosynthetic capacity. Objectives: To identify the association of dyslipidemia with various characteristics in chronic liver disease patients. Patients and meth­ods:  This cross-sectional study was conducted at the Department of Medicine, Civil Hospital, Karachi. The study was conducted between 1st July to 31st December 2017. A total of 211 adults with chronic liver disease were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our study identified family history of dyslipidemia as an independent risk factor for dyslipidemia, which is consistent with several previous studies ( 9 , 28 ). While the exact mechanisms by which family history of dyslipidemia increases the risk of dyslipidemia are not fully understood, it is believed that genetic factors may play a role ( 29 , 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our study identified family history of dyslipidemia as an independent risk factor for dyslipidemia, which is consistent with several previous studies ( 9 , 28 ). While the exact mechanisms by which family history of dyslipidemia increases the risk of dyslipidemia are not fully understood, it is believed that genetic factors may play a role ( 29 , 30 ).…”
Section: Discussionsupporting
confidence: 93%